Variation on Body Weight and Body Dimension of Buffalo in Kabaena Island, Bombana, Southeast Sulawesi - Rusdin, Muh.; Nafiu, La Ode; Saili, T.; Rahadi, S. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Variation on Body Weight and Body Dimension of Buffalo in Kabaena Island,Bombana, Southeast Sulawesi